Penatalaksanaan Fisioterapi Pada Bronkitis Kronis Di Balai Besar Kesehatan Paru Masyarakat Surakarta - Kumala Murti, Adhim, Isnaini Herawati, S.Fis, S.Pd, M.Sc (2015)
Scientific Writing is implemented in THE CENTER OF PUBLIC HEALTH PULMONARY SURAKARTA with the purpose of providing information, knowledge and understanding of the management of physiotherapy in the condition of Piriformis Syndrome among physiotherapists and paramedics on the case as well as the community at large. Bronchitis is an inflammation of the bronchi caused by various factors such as smoking, viral infections, air pollution, etc. The problems that arise, among others, issues such as arise shortness of breath, decreased thoracic expansion, spasm of the respiratory muscles, excessive sputum. The method used in this scientific writing writer did an experiment in the form of case studies with descriptive data analysis. This discussion aims to express how far the results obtained or effectiveness of Infrared and Chest physiotherapy on the condition Chronic bronchitis in patients with Bp. S is 54 years old. Results showed that during the 6 times obtained therapy: results of a decrease in breathlessness of T1: 5, became T6: 4. Increased thoracic expansion in the axilla of T1: 3, became T6: 3, on intercostalis V of T1: 3, became T6: 4, on xiphoideus of T1: 3, became T6: 4. Decrease spasm of the respiratory muscles of T1: there is, becomes T6: None. Sputum decrease of T1: There is, becomes T6: Reduced. Conclusions and suggestions: we can conclude there is success in increasing thoracic expansion, there is a reduction in spending sputum, loss of muscle spasm contained breathing apparatus in percotalis major muscles and upper trapezius, and reduced breathlessness. The next suggestion is to maintain the health of themselves and the environment around the patient's home.